Self-expanding stents based on shape memory alloys and shape memory polymers - Orouji Omid, Samira; Goudarzi , Zahra; Momeni Kangarshahi , Leila; Mokhtarzade, Ali; Bahrami , Fateme (Journal of Composites and Compounds, 2020)
A stenotic vessel can be opened using net-shape tubes called “stents” leading to the restoration of the bloodstream. Compared to the commonly used stainless steel stent, self-expandable stents have some advantages. They do not suffer from the risks of damage to the vascular tissue due to the balloon expansion. Moreover, overexpansion for compensating the elastic recoil is not needed, and there is no constant force applied on the artery until the occlusion of the device by the artery stops. However, the stent cannot restore the original dimensions of the vessel in the case of calcified plaques. Self-expandable stents can be utilized for the treatment of atherosclerotic lesions in the carotid, coronary, and peripheral arteries. Shape memory alloys (SMAs), mainly NiTi (nitinol), are employed for self-expandable vascular stent applications. Nitinol is widely applied for medical devices and implants due to its excellent fatigue performance, mechanical properties, and biocompatibility, which make this alloy suitable for long-term installations. Other materials used for self-expandable cardiovascular stents are shape memory polymers (SMPs). Shape memory effect is triggered by the hydration of polymers or temperature change preventing the collapse of small blood vessels. This review has focused on the mechanisms and properties of SMAs and SMPs as promising materials for stent application.